COLORECTAL CANCER: UPDATE ON DIAGNOSIS, PREVENTION AND TREATMENT - Vítor Brasil; Aldo Cunha Medeiros; Giovana Medeiros Oliveira Pinto; Arthur Ramalho Cunha Lima; Cibele Souza Abbott; Letícia Medeiros Fernandes; Gabriel Emiliano Medeiros Loiola (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Background: Colorectal cancer (CRC) is the third most common cancer worldwide, and surgical treatment remains the first-line treatment to provide a cure. Objective: This review aimed to provide insights into the disease progression, currently available diagnosis, immunology, genetics, treatment options, their challenges, and future perspectives. Results: Despite advances in surgical techniques, chemotherapy, and radiotherapy, colorectal cancer remains the second leading cause of cancer-related deaths worldwide. For early-stage CRC, endoscopic treatment, including endoscopic mucosal resection and endoscopic submucosal dissection, has been performed. The use of nutraceutics, probiotics and natural products were discussed. Conventional open surgery has evolved into laparoscopic and robotic surgery. Furthermore, multidisciplinary treatment is needed to cure CRC completely. Other novel delivery strategies continue to be investigated, including ligand-based targeting of CRC cells.